Direct synthesis and crystal structure of a novel tetranuclear Co2IIIFe2III Schiff base complex - Chygorin, Eduard Nikolaevich; Kokozay, Vladimir Nikolayevich; Omelchenko, Iryna Vasylivna; Rusanova, Julia Anatoliyivna (European Journal of Chemistry, 2020)
The title compound, tetra(µ-2-3-(2-oxybenzylideneamino)-1-hydroxypropan-2-olato)-4-nitrophenolatedi-cobalt(III)-di-iron(III) dimethylsulfoxidehexasolvate, crystallizes in the monoclinic space group P21/c and represent the first example of heterometallic CoIII-FeIII complex with 3-((5-nitro-2-hydroxybenzylidene)amino)propane-1,2-diol/2-(((2,3-dihydroxy propyl)iminio)methyl)-4-nitrophenolate) - a hydroxyl rich Schiff base ligand which was obtained in situ. Crystal data for C52H74Cl2Co2Fe2N8O26S6 (M = 1720.01 g/mol): monoclinic, space group P21/c (no. 14), a = 16.353(3) Å, b = 15.234(2) Å, c = 15.201(3) Å, β = 113.99(2)°, V = 3460.0(12) Å3, Z = 2, T = 173(2) K, μ(MoKα) = 1.225 mm-1, Dcalc = 1.651 g/cm3, 14130 reflections measured (5.7° ≤ 2Θ ≤ 57.266°), 7748 unique (Rint = 0.1051, Rsigma = 0.2148) which were used in all calculations. The final R1 was 0.0914 (I > 2σ(I)) and wR2 was 0.2279 (all data). The metal ions have distorted octahedral coordination geometry and are joined in a tetranuclear Co2Fe2(µ-O)6 core by O-bridging atoms from the ligand. There are numerous intermolecular interactions occurring between the components of the crystal: π-hole interaction between NO2···NO2 groups of the ligands, short S···S, O···O and C··· C interactions and weak and strong hydrogen bonds.